KEBERADAAN BAKTERI TERBAWA LABA-LABA PADA TANAMAN CABAI DI LAHAN AGROEKOSISTEM KABUPATEN BANYUMAS, PROVINSI JAWA TENGAH - Tarjoko, Tarjoko; Mugiastuti, Endang; Oktaviani, Eka; Bahrudin, Muhammad; Suroto, Agus (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
Spiders are the main natural enemies (predators) for pests that attack crops. Knowledge about the relationship between Arthropods found on agricultural land and the bacteria carrying these animals, which are symbiotic, still needs to be found in Indonesia. Spiders are important biocontrol agents in agricultural land. This study examined the relationship between bacteria potentially carried by spiders, as members of the Phylum Arthropoda, in chili plants grown in agroecosystems. This study aimed to determine the presence of bacteria carried by spiders in chili planting areas of the Banyumas Regency. This study found a species of spider (Oxyopes lineatipes) collected from chili crops in 3 (three) sub-districts in Banyumas Regency. From these spiders, 5 (five) bacteria isolates were found, both from inside the body and from the surface of the spider's body. The results of the hypersensitivity test showed that 2 (two) isolates were non-pathogenic bacteria, while the other 3 (three) isolates had potential as plant pathogens. However, further research is still being carried out regarding identifying the bacterial species found.